Development and Validation of TQM Constructs: The Philippine Experience - Talavera, Ma. Gloria V (Gadjah Mada International Journal of Business, 2004)
This study was conducted to determine the critical components of a Total Quality Management program (referred to as TQM constructs) and the specific strategies, policies and programs that should comprise each TQM construct (referred to as TQM elements); and to validate these TQM constructs in selected companies in the Philippines. Development of the TQM constructs involved the theoretical derivation of the TQM constructs from literature. Validation of the TQM constructs involved a two-stage survey determining the critical components perceived important by managers and assessing the extent by which these critical TQM program components are adopted. Assessment of the instrumentâs reliability was done through the Internal Consistency Method with Cronbach coefficient alpha as the relevant coefficient while content and construct validity were done through panel review and Exploratory Factor Analyses, respectively.Results of the first survey indicate a slight deviation in what is perceived as critical components of a quality management system vis-a-vis the original 72 TQM elements. In general, the elements pertaining to a TQM construct as theoretically derived no longer formed part of such construct but merged with other elements in another TQM construct where it shared similarity in functions. This implies that under Philippine context, especially when using perception of importance as the basis for scale development, the integration of activities, strategies and functions associated with TQM program adoption is perceived by respondent managers as more critical. The study presented the multi-functional and multi-dimensional aspects of the TQM constructs. The resulting 35 critical TQM items were further validated in Survey 2. The TQM factors pertaining to the adoption of quantitative techniques in quality management as well as the incentive and reward system were rated lowest in terms of adoption.